PENGUATAN MANAJEMEN SISTEM INFORMASI KOMUNITAS PONDOK SENI BATU - Ardhian, Dany; Rohman, Ahmad Syarifuddin; Rizal, Maulfi Syaiful; Anggrian, Mayang (Universitas Negeri Surabaya, 2025)
Pondok Seni Batu is a community that accommodates most artists in Batu City, East Java. The existence of this community is strategic in the art ecosystem in Batu City. However, this community does not yet have a representative and publicly accessible platform related to its artists, even though the visibility of the artists' information can support the existence of the community and reach a wider audience. This community service is carried out with the aim of (1) expanding the reach of information in the form of a digital platform containing artist profiling and studio mapping to read the artistic laboratory at Pondok Seni Batu, (2) strengthening information management by mapping information systems, (3) profiling artists, studio mapping, and (4) maintaining the continuity of information availability by providing creative writing assistance to young members of the community. This service will produce a profile of Pondok Seni Batu artists and a map of studios in the community. The availability of an information platform containing the two things above can help Pondok Seni Batu for resource mapping, achieving public visibility and building stronger networks.